Tujuan Pendidikan Islam dalam Mencetak SDM Unggul - Mila Mahmudah (Jurnal Keislaman, 2020)
Since the beginning of the development of Islamic education has stood upright on two very important basic sources namely the Al-Quran and the sunnah of the prophet in the sacred scripture contained verses of mufasshalat (detailed) and verses of mubbayyinat (which provide proof of truth) that encourage humans to study and write and to study, think about and analyze the creation of heaven and earth. Islam since its inception shows the importance of education for human life. The first verse received by the prophet Muhammad is iqro "which contains a message about the command to deceive the potential of human reason, and that is at the core of education in Islam. However, it must be recognized that Islamic education at that time did not yet have a formal and systematic form, because the role of education at the beginning of the development of Islam was still limited to efforts to spread Islamic da'wah in the form of monotheism and religious ritual practices. While the teachings of religion that must be obeyed in human life, turned into mere spectacle. All show that the progress of science and technology in the 20th century, apparently not only brought something positive to human life, but also had a negative impact. By looking at various events that identify the lack of understanding of morality above, to provide a strong foundation for humans to come, it is necessary to innovate moral cultivation in the world of education or better known as moral education. In the world of education or better known as moral education. Whereas moral education is not far from implementing Islamic education. Thus the mastery and application of science and technology needs to be developed on the basis of ethics, morality and spiritual (imtaq) in the development of facing the era of improvement of science and technology, national development should also necessitate the importance of the value of faith and piety (imtaq) towards God. So as to create superior human resources according to Islam and be able to deal with the development of the era and era of globalization.